Pengaruh Kualitas Pelayanan Administrasi Keuangan Terhadap Kepuasan Mahasiswa di STMA Trisakti - Widdhisiadji, Bayu; Laratmase, Antonia Junianty; Risdandi, Arie; Fitriyanti, Novi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research was conducted at Trisakti Schcool on Insurance College (STMA Trisakti). This research aims to determine the influence of the quality of financial administration services on student satisfaction at STMA Trisakti and to determine the extent of influence of the quality of financial administration services on student satisfaction at STMA Trisakti. Service quality is a reflection of consumer evaluative perceptions of the services received at a certain time. Service quality is determined based on the level of importance of the dimensions in the service. Financial Administration includes the arrangement and determination of policies in the procurement and use of finance to realize all the main tasks in the organization so that they can run effectively and efficiently. The population in this study was 600 student and the sample was taken by simple random sampling method using the Slovin formula, namely 30 students. This research method uses a quantitative approach with a survey design, while the data collection method uses a questionnaire method, then tested with a data analysis method using SPSS. The method used is descriptive-quantitative with linear regression analysis. The results of this study indicate that Financial Administration Services significantly influence Student Satisfaction at STMA Trisakti, with the contribution level of the quality of financial administration services to student satisfaction reaching 86.1%, calculated using the coefficient of determination analysis (R2). Thus, it can be concluded that the Quality of Financial Administration Services has a significant influence on Student Satisfaction at STMA Trisakti.